Analysis of Changes in ACM Performance in PK-XXX Aircraft with Modification of Cleaning Method to Get a Comfortable Temperature - Antonius Angga Andriawan; Nanang Ruhyat; Michael Kirkland Ngala (Journal of Integrated and Advanced Engineering (JIAE), 2022)
Airplanes are a mode of transportation that people are interested in because they have a relatively short travel time and long distances. Therefore, aircraft is a means of transportation with a high level of safety. One level of safety comes from the aircraft's Air Conditioning (AC) system, which functions as a temperature controller for the aircraft during flight and as a pressure protector during flight. Various components make up an aircraft AC system, one of which is the Air Cycle Machine (ACM). Where the ACM changes the temperature to extremes from hot to cold, the ACM becomes fouling, thereby reducing the performance of the ACM itself and causing an increase in the cabin temperature of the aircraft. This problem was solved by a different cleaning method, first using Aluminum Solution and second without using Aluminum Solution. The difference in cleaning methods aims to determine the right cleaning method to overcome the existing problems. The results showed that power without using aluminum solution gave 49.802 kJ/s in 5 minutes and 54.771 kJ/s in 10 minutes, while power using aluminum solution showed 40.1705 kJ/s in 5 minutes and 61.4155 kJ/s in 10 minutes. This indicates that the use of Aluminum solution requires greater power after the ACM rotates for 10 minutes, affecting the efficiency of the ACM itself. The results prove that the cleaning method without aluminum solution gives results of 140.6% at 5 minutes and 90.34% at 10 minutes compared to before.